Investigating the Oral Health among Individuals with Depression and Anxiety - Dr. Khaliqa tul Zahra; Dr. Resham Hafeez; Dr. Samman Hassan; Dr. Usman Manzoor Warraich; Dr. Asad Farooq; Dr. Umar Farooq Khan; Iqra Akram, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Depression and anxiety are widespread mental health disorders that can have a major influence on oral health. People with these conditions may experience poor oral hygiene, dental caries, and other oral health problems. Objective: The purpose of this study was to investigate the oral health status of individuals with depression and anxiety. Methods: This quantitative research used a cross-sectional study design involving 100 individuals (50 with depression and 50 with anxiety), Ages between 18-60 years. In a six-month research period, the non-probability consecutive sampling technique was employed. The data was obtained from patients through Oral Health Impact Profile (OHIP) questionnaire, the Dental Exam (DMFT index), the Generalized Anxiety Disorder 7-item scale (GAD7), and the Patient Health Questionnaire9 (PHQ9). Results: The statistical analysis was performed using an independent t-test and a chi-square test. Compared to normative data, people with depression and anxiety had worse oral health, as shown by higher DMFT and OHIP scores (p < 0. 001). Oral health results were highly correlated with anxiety and depression scores. Conclusion: This study emphasizes how crucial oral health care is for people who suffer from depression and anxiety. Dental practitioners should be mindful of the possible effects of these disorders on oral health and deliver individualized treatment to address the specific demands of these individuals.